Testifying: a case study of students' perceptions of experiences as members of a school-based youth court at an early college high school - Burks, Tony Burks (2008)
This dissertation explores students' perceptions of--and experiences with--the Student Court at one of the first early college high schools in the southeastern region of the United States of America. Specifically, I provide a mosaic of narratives of former students who served--and current students who are serving--as members of a school-based youth court. By the late 1990s youth courts--also called student courts--developed and expanded exponentially when states across North America began to capitalize on the promise of positive peer pressure. Few studies have examined the effectiveness of youth courts and its members. Because of the emergent literature about youth courts, little is known about the impact of youth courts on participants from justices and peer-advisers to clerks and accused students. The research questions of the doctoral research study were (1) How do members perceive their experiences on a school-based youth court? and (2)How do members of a school-based youth court see themselves developing as leaders? As the founding (and former) principal-director of University Academy (UA), I served as adviser to three student organizations--including its student court--and used my undergraduate college experiences to shape the high school's overall student leadership development philosophy. I envisioned student organizations as vehicles for developing problem-solving skills; transferring knowledge and understanding to other disciplines; and sparking interest in other curricular and co-curricular activities. I believed this approach would fulfill UA's mission and simultaneously enable students to be self-directed lifelong learners who are prepared to succeed in higher education and in the changing world beyond